Power factor correction AC-DC boost converter using PI-hysteresis current control - Mariam K. Shehata; Hossam Eldin Mostafa Attia; Basem E. Elnaghi; Nagwa F. Ibrahim (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The AC line input voltage is frequently rectified by single-phase diode rectifiers and filtered using sizable electrolytic capacitors. The capacitor draws current in brief pulses, so harmonics distort the line current, resulting in high losses. Harmonics and line current distortions harm the unity power factor and efficiency. This article adopts a simple single-stage AC-DC converter with a high-power factor and low total harmonic distortion. The PI hysteresis current control was utilized to reduce the total harmonic distortion and increase the power factor at full load. The PI controller was added to the outer voltage loop to regulate the output voltage. Ziegler-Nichol's tuning method was used to determine the controller gain levels. Simulation results were obtained for the AC-DC converter at a constant switching frequency to show the benefits of the proposed control method, which has a low total harmonic distortion and a high-power factor compared with cases without a controller. The proposed control method is accurate and efficient for achieving the power factor correction converter. Besides, the proposed control was stable during dynamic and steady-state responses.